Prediksi Tingkat Kesejahteraan Masyarakat Di Kelurahan North Wangurer Menggunakan Regresi Linear Berganda - Wikarsa, Liza; Pandelaki, Steven; Sumajouw, Karen (Jurnal Pekommas, 2023)
The level of social welfare in a country can determine the quality and condition of the country itself. North Wangurer sub-district is in Madidir District, Bitung City, with a population of around 750 households. The level of community welfare in this sub-district is solely based on the monthly income obtained from each community which is regarded to be ineffective. Thus, this research aimed to predict the level of community welfare at this sub-district using the multiple linear regression method. It was hoped that this research could provide insights for the North Wangurer sub-district office to make more effective policies/decisions to increase the level of welfare in hope of eradicating poverty and equitably distributing social assistance to the targetted households. There were four independent variables employed in this research such as income, education, occupation, and the number of family members. Meanwhile, the dependent variable was the level of community welfare consisting of Pra-KS, KS-I, KS-II, KS-III, and KS-III Plus as acknowledged by BKKBN. The results revealed that the level of community welfare for the North Wangurer sub-district was in Prosperous Family III Plus (Level 5). Most of the families (98,7%) in this sub-district can meet all basic needs, social psychology and its development, and self-accountability (self-esteem).